1997
DOI: 10.1095/biolreprod56.3.674
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphorylation Is Associated with Capacitation of Human Sperm In Vitro but Is Not Sufficient for Its Completion1

Abstract: Capacitation is a prerequisite step that mammalian sperm must take before being able to undergo the acrosome reaction (AR). The molecular mechanisms of this process remain incompletely understood and can be studied only in vitro. Human sperm preparation for insemination of oocytes requires the removal of seminal plasma and incubation in defined media that usually contain albumin and calcium. In various conditions of capacitation, we have studied the relationship between protein tyrosine phosphorylation as meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
0
2

Year Published

1998
1998
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 45 publications
8
35
0
2
Order By: Relevance
“…2). For instance, initial studies conducted with the mild zwitterionic detergent, CHAPS, revealed a complex pattern of phosphotyrosine proteins whereas those performed with a more stringent SDS-based solubilization, were biased by the presence of two predominant proteins of approximately 85 and 105 kDa, as previously reported (Emiliozzi and Fenichel, 1997). Overexposure of the latter blots revealed a more complex pattern of tyrosine phosphorylation, approximating that seen in the CHAPS extract (Fig.…”
Section: Lectin Labelling Of Live Spermatozoasupporting
confidence: 60%
“…2). For instance, initial studies conducted with the mild zwitterionic detergent, CHAPS, revealed a complex pattern of phosphotyrosine proteins whereas those performed with a more stringent SDS-based solubilization, were biased by the presence of two predominant proteins of approximately 85 and 105 kDa, as previously reported (Emiliozzi and Fenichel, 1997). Overexposure of the latter blots revealed a more complex pattern of tyrosine phosphorylation, approximating that seen in the CHAPS extract (Fig.…”
Section: Lectin Labelling Of Live Spermatozoasupporting
confidence: 60%
“…These phosphorylations should not be considered strictly indicative of full capacitation in ram sperm, as described in human (Emiliozzi & Fenichel 1997) and boar (Tardif et al 2003), where protein tyrosine phosphorylation alone was not sufficient for the completion of capacitation. These data indicate that the signal transduction mechanisms of capacitation in ram sperm differ from those in other mammals, which suggests that species specificities might exist with respect to this process.…”
Section: Discussionmentioning
confidence: 99%
“…In one spermatozoon the progesterone interacts with a cell surface steroid receptor, causing an immediate increase in [Ca], but in other sperm their action was on the membrane phospholipids not inducing AR [2]. Several reports have shown the capacitating effect of progesterone on ejaculated spermatozoa obtained with two layers of Percoll, but those effects cannot be addressed to other sperm parameters as DNA stability or plasma membrane integrity [4,5].…”
Section: Discussionmentioning
confidence: 99%